Faith and Empowerment among Bangladeshi Muslim Women - Md. Abdullah Al Mamun; Md. Nadim Hossen (Universitas Islam Internasional Indonesia (UIII), 2025)
This study explores whether Islam in Bangladesh supports or restricts women's empowerment. Using qualitative analysis of peer-reviewed literature, policy documents, and digital content, the research examines how religious teachings, cultural norms, and social realities interact. Although Islamic teachings emphasize justice, consent, and women's economic rights, these ideals are often unevenly applied due to patriarchal customs, informal dispute parties, and selective religious interpretations. The findings show that practices such as wearing the hijab, praying, and studying the Quran help many women build discipline, dignity, and social capital, which strengthens their confidence, mobility, and voice. At the same time, the same religious spaces, both offline and online, can become restrictive through social monitoring, ‘religious vigilantism’, family norms, and barriers in the job market. While legal protections and systems such as microfinance create new opportunities, their impact often remains limited because of men’s mediation, institutional weakness, and poor enforcement. Overall, the study argues that women's empowerment should not be viewed only through a secular religious divide but through a faith-sensitive lens. It highlights the need for justice-based religious education, inclusive religious leadership, digital safety and literacy, and stronger implementation of legal rights. The findings suggest that religion can function both as a resource and a barrier, and its impact depends on factors such as class, location, disability, and access to digital platforms.